A Level-Based Approach to Prioritize Telecommunications R&D - Joana Fialho; Pedro Godinho; Jo ̃ao Paulo Costa; Ricardo Afonso; José Gonc ̧alo Regalado (Journal of Telecommunications and Information Technology, 2023)
In this paper, an approach to evaluate R&D projects in telecommunications is presented. These projects have particular features that cannot be properly incorporated by classical evaluation methods. This approach incorporates different criteria, both quantitative and qualitative, and also management flexibility and uncertainty. Thus, it is an approach that can be applied to real data of R&D projects in a telecommunications company.